The impact of firms’ social media initiatives on operational efficiency and innovativeness - Lam, Hugo K.S.; Yeung, Andy C.L.; Cheng, T.C. Edwin (Journal of Operations Management, 2016)
Social media have been increasingly adopted for organizational purposes but their operational implications are not well understood. Firms’ social media initiatives might facilitate information flow and knowledge sharing within and across organizations, strengthening firm‐customer interaction, and improving internal and external collaboration. In this research we empirically examine the impact of social media initiatives on firms’ operational efficiency and innovativeness. Taking the resource‐based view of firms’ information capability, we consider firms’ social media initiatives as strategic resources for operational improvement. We posit that firms’ social media initiatives enhance dynamic knowledge‐sharing routines through an information‐rich social network, leading to both operational efficiency and innovativeness. Collecting secondary data in a longitudinal setting from multiple sources, we construct dynamic panel data (DPD) models. Based on system generalized method of moments (GMM) estimation, we show that firms’ social media initiatives improve operational efficiency and innovativeness. We identify the importance of an information‐rich social network to the creation of knowledge‐based advantage through firms’ social media initiatives, and discuss the theoretical and managerial implications from the perspective of operations management.